Neuro-Behcet: The Value of Transcranial Doppler - Goma, Samar H.; Selim, Zahraa I.; Shehata, Ghaydaa A.; Sayed, Doaa Samir; Ahmed, Dalia (Aktuelle Rheumatologie, 2019)
Abstract Neurological involvement in Behcet disease (BD) is one of the most serious causes of long term morbidity and mortality and can be found in up to 49% of cases. There are 2 main types of CNS involvement, parenchymal and non-parenchymal. Transcranial Doppler (TCD) ultrasonography provides a relatively inexpensive, noninvasive, evaluation of the haemodynamics within intracranial arteries.Material and Methods Case control study of 15 patients with NBD all of them fulfilled the criteria of the International Study Group for Behcet’s disease and fifteen apparently healthy volunteers age and sex matched. All patients and healthy controls were examined by TCD. Cranial Magnitic Resonance Imaging (MRI) examination was performed to the patients group.Results Transcranial Doppler showed significant decline in the mean velocity (MV) of all the examined cerebral arteries in all NBD patients with the highest significant decrease in the vertebral artery (VA). On the other hand, a significant increase in the pulsatility index (PI) was detected only in the posterior cerebral artery (PCA). Regarding MRI examinations of our patients, 7 of 15 (46.7%) patients had parenchymal lesions, 13% had vascular lesions coexisting with parenchymal lesions (mixed). The parenchymal were located in the periventricular and superficial cerebral white matter, thalamus and brainstem followed by the cerebellum. Vascular lesions were dural and transverse sinus thrombosis.Conclusion TCD provides a sensitive and accurate bed-side non-invasive imaging tool for the detection of flow pattern abnormalities in patients with NBD. MRI remains the gold standard for diagnosis.